Model Dinamika Spasial Perubahan Tutupan Lahan dan Daya Dukung Lahan Permukiman Kota Ambon Tahun 2031 - Juan Steiven Imanuel Septory; Philia Chisti Latue; Heinrich Rakuasa (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2023)
The rate of population growth that continues to increase in Ambon city with the availability of suitable land is relatively constant, resulting in inconsistencies between land requirements and available land. This study aims to analyze land cover changes in Ambon City in 2013, 2018, 2023 and predict land cover in 2031 using the Cellular Automata Markov Chain (CAMC) and the carrying capacity index of residential areas. The driving factors used in this study were elevation, slope, distance from the coastline, distance from the main road, distance from the river, distance from the center of economic activity and distance from protected areas. Based on the predictions of the Cellular Automata Markov Chain model in 2031, the built-up land cover has increased in area to 4,958.33 ha or 49,583,268 m2, with a predicted population of Ambon City in 2031 of 2,445,961 people. The calculation of the carrying capacity of residential land in 2031 in Ambon City results in the carrying capacity index of residential land of 1.27 m²/capita, meaning that if DDPm > 1 indicates the carrying capacity of residential land is high and still able to accommodate residents to live and build houses in the area. In other words, Ambon City can still accommodate an increase in settlements of 1.27 m²/capita.